Observation of photon recycling in strain-balanced quantum well solar cells - Johnson,JC; Ballard,IM; Barnham,KWJ; Connolly,JP; Mazzer,M; Bessiere,A; Calder,C; Hill,G; Roberts,JS (Applied Physics Letters, 2007)
Photon recycling in strain-balanced quantum well solar cells grown on distributed Bragg reflectors has been observed as a suppression of the dark current and a change in electroluminescence spectra.Comparing devices grown with and without distributed Bragg reflectors we have demonstrated up to a 33% reduction in the ideality n=1 reverse saturation current. Furthermore, to validate the observations we demonstrate how both the measured dark currents and electroluminescence spectra fit very well to a photon recycling model. Verifying our observations with the model then allows us to calculate optimized device designs.